Continuous ASL perfusion fMRI investigation of higher cognition: Quantification of tonic CBF changes during sustained attention and working memory tasks - Kim, Junghoon; Whyte, John; Wang, Jiongjiong; Rao, Hengyi; Tang, Kathy Z.; Detre, John A. (NeuroImage (Orlando, Fla.), 2006)
Arterial spin labeling (ASL) perfusion fMRI is an emerging method in clinical neuroimaging. Its non-invasiveness, absence of low frequency noise, and ability to quantify the absolute level of cerebral blood flow (CBF) make the method ideal for longitudinal designs or low frequency paradigms. Despite the usefulness in the study of cognitive dysfunctions in clinical populations, perfusion activation studies to date have been conducted for simple sensorimotor paradigms or with single-slice acquisition, mainly due to technical challenges. Using our recently developed amplitude-modulated continuous ASL (CASL) perfusion fMRI protocol, we assessed the feasibility of a higher level cognitive activation study in twelve healthy subjects. Taking advantage of the ASL noise properties, we were able to study tonic CBF changes during uninterrupted 6-min continuous performance of working memory and sustained attention tasks. For the visual sustained attention task, regional CBF increases (6–12 ml/100 g/min) were detected in the right middle frontal gyrus, the bilateral occipital gyri, and the anterior cingulate/medial frontal gyri. During the 2-back working memory task, significantly increased activations (7–11 ml/100 g/min) were found in the left inferior frontal/precentral gyri, the left inferior parietal lobule, the anterior cingulate/medial frontal gyri, and the left occipital gyrus. Locations of activated and deactivated areas largely concur with previous PET and BOLD fMRI studies utilizing similar paradigms. These results demonstrate that CASL perfusion fMRI can be successfully utilized for the investigation of the tonic CBF changes associated with high level cognitive operations. Increased applications of the method to the investigation of cognitively impaired populations are expected to follow.